Healthcare experiences of homeless pregnant women - Keila Cristina Costa Barros; Rita de Cássia Rocha Moreira; Mariana Silveira Leal; Tânia Cristiane Ferreira Bispo; Rosana Freitas Azevedo (Universidade Federal do Ceará, 2020)
Objective: to understand healthcare experiences from the perspective of women who are or were pregnant while in homelessness. Methods: qualitative study based on Heideggerian phenomenology adapted to the field of health. There were ten participants. The technique of phenomenological interview and a semi-structured instrument were used. The comprehensive analysis methodically followed the stages of phenomenological reduction, construction,and destruction. Results: the existence of pregnant homeless women represents difficulties, discrimination, violence, prejudice, racism,and vulnerability. It is a violation of human dignity, revealing specificities and nuances of the triad women-maternity-street. Conclusion: the research made it possible to understand that healthcare, from the perspective of women who are pregnant while homeless, offers risks both to the mother and to the child. Both the self-care and the healthcare offered by health workers and services is precarious and has weaknesses, being different from any type of care that could be understood as solicitous, zealous, and concerned.